Vaqi'ah-'i kashf-i hijab : (Sazman-i Madarik-i Farhangi-yi Inqilab-i Islami; Mu'assasah-i Pazhihish va Mutali'at-i Farhangi, 1994)
'Unveil: non-published documents about unveil during the reign of Reza Shah'